Uji Laboratorium Pengaruh Kemiringan Lereng Terhadap Kejadian Longsoran Aliran Debris Pasir Merapi - Bayu Seto Waseso Utomo; Jati Iswardoyo; Ruzardi Ruzardi (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2020)
The debris flow that happen on the of Mount Merapi is really hard to be seen, therefore, it is necessary to conduct laboratory-scale simulations to know when debris flows will happen as regard to rainfall intensity and the slope of Mount of Merapi. This research examines the correlation between the slope and the potential for debris flow at 25 mm/h rainfall intensity. This will be a reference for early warning of landslides on Mount of Merapi. This research uses a tool such as flume that sized 3 x 5 x 0,15 m as a model of slope of Mount of Merapi, and artificial rainfall apparatus as the rain simulator. The simulation is conducted using five years rainfall intensity of 25 mm/h in combination of slope i.e. 15, 20, 25, 30 and 35 degrees whereas the material used to represent the sediment is in form of sand taken from Gendol River upstream with 4,75 mm passing mesh sieves. The result of this simulation is the steeper the slope is, the faster the duration for the rain to cause debris flow. This research can be continued with change variation of rainfall intensity to understand the debris flows behavior. Keywords: Debris flow, Mount of Merapi, laboratory test, rainfall intensity, flume model